Exploring African Leadership: Traditions, Values, and Contemporary Practices - Zvavahera, Promise (Journal of Leadership in Organizations, 2025)
Introduction/Main Objectives: This study examines the philosophical influence of African traditions, particularly Ubuntu, on servant leadership in Africa and beyond. It seeks to understand how Africa’s rich cultural heritage can shape leaders who prioritize service and employee well-being. Background Problems: Leadership models from the Global North often fail to capture Africa’s unique cultural dynamics, prompting calls for servant leadership rooted in African values. This study explores the intersection of traditional leadership, contemporary practices, and their impact on governance and socio-economic development. Novelty: This study explores the uniqueness of African leadership by analyzing the interplay between traditional values, cultural heritage, modern practices, highlighting how indigenous philosophies can influence contemporary decision-making and leadership dynamics in a global context. Research Methods: Using a systematic literature review, the study draws insights from 59 peer-reviewed articles, online databases, reports, and textbooks. Sources include JSTOR, Web of Science, Google Scholar, and Scopus. Findings/Results: Findings indicate that Ubuntu embodies values such as humanity and collective responsibility, forming a strong foundation for servant leadership models applicable beyond Africa. The literature highlights gaps in Global North models, which often overlook African leadership realities. Additionally, traditional teachings and oral histories contribute to the sustainability of servant leadership in Africa. Conclusion: This study underscores the significant contribution of Ubuntu to the global leadership discourse. It demonstrates the potential of this philosophy to foster ethical, community-driven leadership that transcends cultural boundaries and can be adapted and applied in diverse contexts worldwide.